The Technology Roadmapping Method and its Usage in Chemistry - Vasconcelos Loureiro,Aline Marta (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2010)
Technology roadmapping is a widely used technique in the industry for the development of long term planning strategies, making it possible to align market, product and technology over time. This article offers a brief review of this tool, covering the definitions of the terms technology roadmap and technology roadmapping, the types and formats of roadmaps, the structure of roadmaps, the processes of operation/adaptation of roadmapping, challenges and the key successful factors in implementing the roadmapping and its usage. Finally, an overview of public domain roadmaps is given, with special highlight to the ones related to Chemistry.